PELATIHAN SCREEN PRINTING SEBAGAI UPAYA PEMBERDAYAAN ANAK-ANAK PANTI ASUHAN AISYIAH KOTA BUKITTINGGI - Syafei Syafei Syafei; maltha Kharisma; Ariusmedi Ariusmedi (Ranah Seni, 2019)
Abstract: Most of the children who are in the Aisyiah Orphanage in Bukittinggi City do not yet have reliable skills, so if they leave the institution it is feared that they cannot be independent. For that they are fostered by providing various types of skills as a provision of life, so that after leaving the institution they can work and even create new jobs. Unfortunately the skills provided at this orphanage are very limited and less varied. The factors causing the variety of types of skills provided or implemented in this orphanage are; 1) lack of expertise from various types of skills and 2) lack of funds for its implementation, although there is assistance from the government and the community but it is not sufficient. The types of skills that are often provided especially for men are sewing and carpentry sewing. While the types of skills related to art have never been given. Whereas most of the children's homes (62.1%) have artistic talent. For this reason, the head of the orphanage expects training in screen printing skills for their foster children. The solution offered to overcome this problem is to conduct practical skills training, namely screen printing. The provisional result of this activity was that in general (84.65%) the children of the Aisyiah orphanage, Bukittinggi City son, had the ability to print well with green printing techniques.